“Che cos’è? Va e de”? Domande, risposte e commutazione di codice in due classi svedesi di italiano L2/LS - Caroline Carlén; Franco Pauletto (Moderna Språk)
This conversation-analytic study investigates the use of code switching (henceforth CS) in three Italian L2 classrooms in Sweden. Specifically, when and why do teachers code switch in their questions? Is the language choice pedagogically motivated? Does the teachers’ language choice have an influence over the students’ language choice in their answers? The data were collected from three beginner-level Italian lessons in two Swedish High Schools. Transcripts of questions in which CS occurred were analyzed using a conversation analytic approach with a focus on sequentiality in relation to the organization of turn allocation, to understand when and why the CS occurs in both questions and answers. In our data teachers use CS when posing questions to the class in two major occasions, namely when the question is followed by a significant silence but also when no discernible silence follows a question. Furthermore, regardless of the language used by the teacher, the students answer in Italian when the questions are task-based, and in Swedish when the questions are off-task.